Advanced deep flux weakening operation control strategies for IPMSM - Pham Quoc Khanh; Ho Pham Huy Anh (International Journal of Electrical and Computer Engineering (IJECE), 2021)
This paper proposes an advanced flux-weakening control method to enlarge the speed range of interior permanent magnet synchronous motor (IPMSM). In the deep flux weakening (FW) region, the flux linkage decreases as the motor speed increases, increasing instability. Classic control methods will be unstable when operating in this area when changing load torque or reference speed is required. The paper proposes a hybrid control method to eliminate instability caused by voltage limit violation and improve the reference velocity-tracking efficiency when combining two classic control methods. Besides, the effective zone of IPMSM in the FW is analyzed and applied to enhance stability and efficiency following reference velocity. Simulation results demonstrate the strength and effectiveness of the proposed method.